Ekranisasi Novel ke Film Dear Nathan: Thank You Salma yang Disutradarai oleh Kuntz Agus - Rizki, Nurpiyah; Hartati, Dian (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2023)
The research was motivated by the numerous movie adaptations of novels that capture public interest. During the process of adapting a novel into a movie, the director makes certain modifications. One such instance is the adaptation of the novel Thank You Salma into the movie Dear Nathan: Thank You Salma. These alterations give rise to both similarities and differences between the novel and the film. The objective of this research is to describe the process of adapting the novel Thank You Salma by Erisca Febriani into the film Dear Nathan: Thank You Salma, directed by Kuntz Agus. The research methodology employed is descriptive qualitative. Data collection techniques involve reading, watching, and taking notes. First, the researchers read the novel. Second, they watched the film to observe and document the process of adaptation. Lastly, the researchers recorded the similarities and differences between the novel and the film, specifically about the adaptation process. The findings reveal that the movie entailed reductions in the plot, characters, and setting, as well as additions to these aspects. Additionally, there were various changes made to the plot, setting, place, and characterization. Furthermore, there were similarities in themes, points of view, language style, and the underlying message conveyed in both the novel and the movie. Despite these changes, the movie successfully attracted a wide audience and received positive feedback on social media, as it addressed social issues related to sexual harassment against women.